Dr Maung Maung : Gentleman, Scholar, Patriot - Taylor, Robert H., 1943- (Book collections on Project MUSE., 2008)
Explores the life of Dr. Maung Maung (1925-94), scholar, soldier, nationalist, internationalist, parliamentarian, public servant, and pioneer amongst post-colonial journalists in Southeast Asia. His life spanned seven decades of political, economic and social turbulence in the country he loved and served, Myanmar.